Um estudo da indústria de tecelagem e produção de sacaria de ráfia no Paraná - Horbus, Eliane (2012)
The present paper is a study about the plastic transformation industry, in the packing sector that acts in the textile industry and in the raffia sacks production located in Parana, focusing in the analysis of that sector development in the same State. Besides, it discourses about the location factors that influenced the industries construction in Guarapuava and Campo Largo, including the survey on the potential of employment creation, on the used labor profile and on the technologies applied in the industrial process. In the theoretical filed, the slight relation between industry studies and geo economics and new geo economy was broached, what provided comprehension on the transformations that occurred in space from the ways of work organization and production. Furthermore, the development of the petrochemistry in Brazil and in Paraná was analyzed. In order to accomplish the objectives of the research, some technical visits to the plants located only in Paraná occurred, using the in loco technique with structured interviews, trying to evidence each factory own characteristics and their respective location factors. At last, a comparative board is presented showing the development of the three industries settled in Paraná and the conclusion about the possible influence of the location factors.